Entre ficções e rupturas: a etnopolítica Borum nas arenas oficiais de resolução de conflitos - João Vitor de Freitas Moreira (2024)
The Borum of Watu, as the Krenak people call themselves, is an indigenous group located in the east side of the state of Minas Gerais, whose political opulence is a nationally known. Crossed by a series of historical violence, this indigenous group is an example of resilience against the indigenous policies put in practice since the times of Brazilian Empire, and victims of developmental policies that find their “best” performance within the persistent contemporary neo-extractive practices. Faced with these macropolitical attitudes with local reflections, the Borum people bring their ethnopolitics into play. And that is what this thesis is all about. I seek to take in the aspects of borum ethnopolitics, combining for this purpose ethnographic research developed since mid-2019. However, in a region known as the “Sertões do Leste”, doing ethnography is a challenge that only under the framework of engaged anthropology it is possible to cover the vicissitudes of a disputed territory in each the Krenak people find themselves. In this context, the conflicts involving the various aspects of the violation against the borum gain prominence in the field of law, over which the indigenous interest is notable. For this reason, it was necessary to combine an anthropology of law with a political anthropology to delve into the intricacies of borum ethnopolitics, whose driving force was possible to identify from a native category: krekmun. This term, translated as wanderings, has some proprieties identified in a meticulous investigation over the effects and traces of political action. These actions have interesting gradations in the field of law, and, specifically, in adjudicatory procedures analyzed from an anthropological perspective that sees the documents of law as artifacts. Presented in two parts and eight chapters, this thesis understands the borum ethnopolitics as a multi-tabular experimental action, which is based on a microphysics of influences whose essential motor is, recursively, the wanderings of the borum people. Ultimately, I conclude that indigenous political action, whose mode of wandering is its driving force, present itself as a “contingently complex experimentation”, whose misunderstandings (méconnaissance) are the starting point for an initial observation of a theory of political action yet to come.